HPV and the Risk of HIV Acquisition in Women - Zayats, Romaniya; Murooka, Thomas T.; McKinnon, Lyle R. (Frontiers in Cellular and Infection Microbiology, 2022)
The risk of HIV acquisition is low on a per-contact basis but increased by transmission co-factors such as other sexually transmitted infections (STIs). Human papillomavirus (HPV) is a prevalent STI that most individuals will acquire HPV in their lifetime. Current HPV vaccines can prevent newly acquired infections, but are largely ineffective against established HPV, complicating worldwide eradication efforts. In addition to being the causative agent of cervical cancer, accumulating evidence suggests that HPV infection and/or accompanying cervical inflammation increase the risk of HIV infection in men and women. The fact that immunological features observed during HPV infection overlap with cellular and molecular pathways known to enhance HIV susceptibility underscore the potential interplay between these two viral infections that fuel their mutual spread. Here we review current insights into how HPV infection and the generation of anti-HPV immunity contribute to higher HIV transmission rates, and the impact of HPV on mucosal inflammation, immune cell trafficking, and epithelial barrier function.